Books, Video Games, and Foul-Mouthed Hollywood Glitteratae: The Supreme Court and the Technology-Neutral Interpretation of the First Amendment - Lee, William E. (Science and Technology Law Review, 2013)
For more than fifty years, members of the Court have disputed whether core First Amendment principles apply equally to all methods of communication. That is, whether technological neutrality is a component of First Amendment doctrine. In Citizens United v. FEC, where the Court struck down a restriction on corporate or union sponsored candidate advocacy distributed via broadcast, cable or satellite, Justice Kennedy issued one of the Court’s strongest statements in favor of technological neutrality. Yet, in FCC v. Fox Television Stations, Inc., which in 2012 presented the Court the opportunity to revisit the diminished First Amendment status of broadcasting, the Court, per Kennedy, punted and instead found that three FCC indecency actions violated the due process clause of the Fifth Amendment. Whether the First Amendment’s protection of broadcasting should be strengthened, in light of changing technological and market features, was postponed for another day. One reading of Fox’s avoidance of First Amendment questions is that among the eight justices participating in the case, there were not five votes in favor of recasting the constitutional status of broadcasting. Hence, Citizens United may be more about the primacy of political speech than a new commitment to technological neutrality. The Supreme Court’s cases involving content-regulation tied to a communication technology are a doctrinal mess. One line of cases, which this Article denotes as technology based, emphasizes the “peculiar problems” of a method of communication as justification for content-based regulation. Foremost in this line of cases are Red Lion Broadcasting Co. v. FCC and FCC v. Pacifica Foundation, where the Court upheld broadcast content regulations that are unacceptable in other media. A second line of cases, denoted as technology neutral, posits that the First Amendment’s hostility to content regulation overrides legislative claims about the distinctive qualities of a communication medium. The most contemporary example of this type of case is Brown v. Entertainment Merchants Association, where the Court in 2011 rejected California’s assertion that the interactive nature of video games justified restricting children’s access to violent video games. In the second line of cases, claims about “peculiar problems” are pushed to the background and the focus is on basic principles such as the invalidity of content discrimination. As this Article reveals, Brown is not truly a video game decision; it is a decision about the constitutional status of violent portrayals. Brown is the paradigmatic technology-neutral analysis. This Article shows Citizens United and Brown offer a useful template for addressing technology-specific restrictions. Courts are ill-equipped to assess rapidly changing media markets. Rather than engage in a sham dialogue about “peculiar problems,” this Article advocates a distinct approach that disfavors content regulation. The Court’s focus should be on first principles instead of transitory facts.